Quality check of pedagogical dough on the higher mathematics on a subject "theory of function of a complex variable" - Larisa V. Limanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This work is devoted to research of quality of pedagogical dough on the subject "Theory of Function of a Complex Variable" in a higher mathematics course which is used for students examination on the second year of SSTU. The degree of difficulty of each task, a variation of test tasks and one of the main characteristics of dough - reliability were estimated for this purpose. A formula KR-20 (on a variation of test tasks); Spirmena-Brown's formula and a formula which uses average coefficient of correlation of all tasks among themselves were applied to calculation of coefficient of reliability. Results of researches showed that for improvement of quality of dough it is necessary to increase number of tasks according to a frequency rate formula, or to change some tasks.